Integration of Religious Tolerance in Fiqh Learning Outcomes in The Merdeka Curriculum at Madrasah - Amar, Abu; Hidayati, Zuhriyah (Fakultas Agama Islam Universitas Billfath, 2025)
This article aims to describe the characteristics, objectives of fiqh and integration of tolerance in the Learning Outcomes (CP) of the Fiqh Subject in the Madrasah Merdeka Curriculum. This qualitative research applies a descriptive method, data obtained from library materials using content analysis to conclude. The results of the study concluded that the characteristics of fiqh in madrasas basically contain regulations on the relationship between Muslims and Allah SWT, between fellow humans, and between humans and the environment. The objective of the fiqh subject is to make students able to practice Islamic law in a plural society. The integration of tolerance in the CP of the fiqh subject at the Madrasah Ibtidaiyah level includes: Tolerance in the implementation of fiqh worship, and rukhsah worship. The Madrasah Tsanawiah level includes: Tolerance of ikhtilaf worship and justice of muamalah. The Madrasah Aliyah level includes: Tolerance of ikhtilaf-fiqh, respecting differences in fiqh thinking, and acceptance of fiqh law and positive law.